PENEGAKAN HUKUM DALAM OTENTISITAS KATOLIK (KENISCAYAAN YANG KEKINIAN) - Michael, Tomy (EDUTECH CONSULTANT, 2018)
Law enforcement is the process of realizing legal desires into reality. What is meant by legal wish is the minds of the law making body formulated in the rule of law. When law enforcement in the study of legal sociology is confronted with law enforcement in criminal law studies then law enforcement actually has a different paradigm. Law enforcement can not run in one corridor regardless of law enforcement in the teaching of other legal fields. In designing academic texts a legislation, in particular the law, should keep in mind the ultimate objective of the law. Sometimes a law only focuses on some legal subject or entire legal subject. When there is a specialization of the subject of law then if the ultimate goal is more directed to religion can use the teachings of Catholicism primarily on love.